COMMUNITY SERVICE EDUCATION ON CHANGES IN COMMUNITY PSYCHOLOGY ABOUT HIGH RISK DETECTION OF MOTHERS AND CHILDREN IN MEDAN TUNTUNGAN DISTRICT - Lenny Sepriani Br. Silalahi; Fistaqul Isnaini; Santalia Laoli (Jurnal Masyarakat Indonesia (Jumas), 2024)
The pregnancy period and the early period of child growth are a very crucial phase of life transition, in which the mother undergoes not only biological changes, but also complex psychological dynamics. Nationally, efforts to reduce the Maternal Mortality Rate (MMR) and Infant Mortality Rate (AKB) remain the government's top priority through various preventive strategies and early detection of complications. However, the success of medical programs in the field often comes up against a wall of perception and psychological conditions of society that are not fully aligned with modern health standards. The program was carried out on December 19, 2024 through interactive counseling methods, early detection demonstrations, and discussions on Increasing awareness and psychological changes in recognizing pregnancy hazards and child risk independently. The results of the evaluation showed a significant improvement in understanding strengthening the clinic's role as an accurate information center to encourage routine checkups. This education is expected to encourage mothers and children to be more proactive in increasing awareness and psychological changes in recognizing pregnancy hazards and child risks independently.